ANALISIS PENGARUH INVESTASI DAN BELANJA PEMERINTAH TERHADAP PDRB DI KOTA PEKANBARU TAHUN 2000 – 2015 - Tampati, Endro; Yusuf, Yusbar; Budiartiningsih, Rahmita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
Development is essentially a multidimensional process that involves changes in social structure, changes in people's attitudes and changes in national institutions. One indicator to measure the success of development within a State is economic growth. Growth itself can be interpreted as a picture of the impact of government policies implemented in the economic field. The area in which the object of research is the city of Pekanbaru. This study uses secondary data obtained from various sources including the Central Bureau of Statistics (BPS) and related Institutions, the method of data analysis using Classic Assumption Test such as Normality Test, Multicolinearity, Autocorrelation, Heteroskedasticity and Hypothesis Testing using the overall regression coefficient (test- F), individual regression coefficient test (t-test), correlation coefficient test (r), and multiple coefficient determination test (R2). The result of this research are: 1) The influence of domestic investment realization (PMDN) and Government Expenditure on Gross Regional Domestic Product of Pekanbaru City is the existence of strong positive influence between independent variable (PMDN and Government Expenditure) to the dependent variable (GRDP). 2). Based on the simultaneous results (F test) found that the three independent variables useDevelopment is essentially a multidimensional process that involves changes in social structure, changes in people's attitudes and changes in national institutions. One indicator to measure the success of development within a State is economic growth. Growth itself can be interpreted as a picture of the impact of government policies implemented in the economic field. The area in which the object of research is the city of Pekanbaru. This study uses secondary data obtained from various sources including the Central Bureau of Statistics (BPS) and related Institutions, the method of data analysis using Classic Assumption Test such as Normality Test, Multicolinearity, Autocorrelation, Heteroskedasticity and Hypothesis Testing using the overall regression coefficient (test- F), individual regression coefficient test (t-test), correlation coefficient test (r), and multiple coefficient determination test (R2). The result of this research are: 1) The influence of domestic investment realization (PMDN) and Government Expenditure on Gross Regional Domestic Product of Pekanbaru City is the existence of strong positive influence between independent variable (PMDN and Government Expenditure) to the dependent variable (GRDP). 2). Based on the simultaneous results (F test) found that the three independent variables used in the study of Domestic Investment and Government Expenditure significantly influence the Gross Regional Domestic Product Pekanbaru with probability (significant) of 0.00 with F count 80.805 . 3) Based on the partial test (t test) it is known that the variable X1 (PMDN) in this study proved that the PMDN variable has a positive and insignificant effect on the PDRB of Pekanbaru City.Key : PMDN, PMA, Government Expenditure, GRDP